Effects of ovarian stimulation protocols on outcomes of assisted reproductive technology in adenomyosis women: a retrospective cohort study - Ge, Li; Li, Yexing; Guan, Shengnan; Cui, Linlin; Chen, Zi-Jiang (Frontiers in Endocrinology, 2023)
Objective: To evaluate effects of different ovarian stimulation protocols on in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) outcomes in infertile women with adenomyosis.We carried out a retrospective cohort study among infertile women with adenomyosis receiving IVF/ICSI treatment, including 257 fresh embryo transfer (ET) cycles and 305 frozen embryo transfer (FET) cycles. In fresh ET cycles, ultra-long, long, short and antagonist protocols were adopted. In FET cycles, patients received long acting GnRH agonist (GnRHa) pretreatment or not. The primary outcome was clinical pregnancy rate (CPR), and the secondary outcomes included implantation rate (IR), miscarriage rate (MR) and live birth rate (LBR).In fresh ET cycles, compared with ultra-long and long protocols, IR (49.7%, 52.1% versus 28.2%, P=0.001) and CPR (64.3%, 57.4% versus35.6%, P=0.004) significantly decreased in short protocol. Similarly, compared with ultra-long and long protocols, a decreased inclination of IR (49.7%, 52.1% versus 33.3%) and CPR (57.4%, 64.3% versus 38.2%) existed in antagonist protocol, although no statistical significance was detected because of strict P adjustment of Bonferroni method (Padj=0.008).Compared with long protocol, LBR in short protocol decreased obviously (48.2% versus 20.3%, P<0.001). In FET cycles, no matter which origin of embryos, there were no statistical differences on IR, CPR and LBR. For women ≥35 years receiving fresh ET, CPR was higher in ultralong and long protocols (52.1%, 50.0% versus 20.0%, 27.5%, P=0.031) compared to antagonist and short protocols. For women ≥35 years receiving FET, compared with ultralong and antagonist protocols, cycles with embryos originating from long and short protocols had higher proportions of long acting GnRHa pretreatment (30.4%,30.00 versus 63.9%, 51.4%, P=0.009). IR (61.1%, 48.6% versus 32.6%, 25.0%, P=0.020) and CPR (58.3%, 48.6% versus 30.4%, 25.0%, P=0.024) in long and short protocols were higher than rates of ultralong and antagonist protocols, but no statistical differences were supported because of strict Bonferroni method (Padj=0.008).In infertile women with adenomyosis, if fresh embryo was planned to transfer, ultra-long or long protocol might be beneficial. If antagonist and short protocols were used, whole embryos were frozen followed by FET was recommended.In FET cycles, embryo derived from different protocols had no impact on pregnancy outcomes.